A comparison between two health care delivery systems using a spatial competition model approach. Issue 1 (1st January 2016) - Nishida, Kiheiji; Yoshida, Atsushi
Abstract : Regional mal-distribution of healthcare providers such as hospitals and clinics is conspicuous in Japan. This study analyses whether Japan's fee-for-service reimbursement system (FFSRS) or its diagnosis procedure combination/per-diem payment system (DPC/PDPS) is the better solution for the problem, with reference to the Hotelling-style spatial competition model. Under FFSRS, we also consider two modes of competition: the Stackelberg case, in which providers can control the number of hospital visits, and the Nash case, in which providers cannot do so. Results indicate that competition under DPC/PDPS is the most intensive of the three modes of competition. To relieve the locational concentration of providers, we also find that DPC/PDPS has a better mechanism than FFSRS.